Prevalência de sarcopenia e fatores associados em pessoas idosas residentes em um município do Rio Grande do Sul - Santos, Michel Pagliarini dos (2025)
The main objective of this study was to estimate the prevalence of sarcopenia among elderly people living in the municipality of Coxilha, Rio Grande do Sul, a territory characterized as rural, and to identify the factors associated with its occurrence. As a secondary objective, we sought to characterize the sociodemographic and clinical profile of the study population. Sarcopenia, defined as the loss of muscle mass accompanied by reduced strength or function, poses a major challenge to healthy aging, especially in territories underrepresented in epidemiological research. This is a cross-sectional, population-based study, part of a dynamic cohort initiated in 2010, which, in 2021, reassessed the previously included older adults and incorporated new residents aged 60 years or older. Data collection was carried out through household surveys using a standardized and pre-coded questionnaire, covering sociodemographic, clinical, cognitive, nutritional, functional, and lifestyle variables. Sarcopenia was classified according to the European Working Group on Sarcopenia in Older People 2 (EWGSOP2), using Lee’s Equation to estimate muscle mass, handgrip dynamometry to assess muscle strength, and an adapted version of the International Physical Activity Questionnaire (IPAQ) to evaluate physical function. Statistical analysis was performed using Poisson regression, estimating prevalence ratios and 95% confidence intervals. A total of 507 older adults were assessed, of whom 60.3% presented sarcopenia or severe sarcopenia, with higher occurrence among individuals aged 80 or older and those without a diagnosis of diabetes mellitus. In the adjusted analysis, advanced age and absence of diabetes remained significantly associated with sarcopenia. The findings highlight the urgent need for local health policies and strategies to prevent and manage sarcopenia, especially in small municipalities, by taking clinical, sociodemographic, and territorial factors into account. This study contributes to the scientific understanding of sarcopenia in semi-rural areas and supports the development of interventions that promote functional aging and quality of life.